Making the Web world-wide: A project in Laos is giving Internet access to villagers without electric - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Making the Web world-wide: A project in Laos is giving Internet access to villagers without electricity, The Economist, September 2002